2020
DOI: 10.1515/zsr-2020-0019
|View full text |Cite
|
Sign up to set email alerts
|

At the intersection of immigration and welfare governance in the United States: State, county and frontline levels and clients’ perspectives

Abstract: The U.S welfare reform of 1996 restricted the eligibility of immigrants and introduced a punitive and devolved workfare system. While previous studies explained state variation in the welfare eligibility rules for immigrants, few studies have examined the intersection of immigration and welfare governance within a state. We choose the Californian welfare-to-work (WTW) program as a case, most likely to be inclusive to immigrants. Analyzing statistics, documents, and interviews at the state, county, and frontlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Policies about immigration and access to welfare systems for immigrants are constantly evolving, leading to confusion and inconsistent implementation. Lanfranconi et al (2020) examined the inclusionary and exclusionary mechanisms that are imposed through regimes, practices, and discourses at multiple levels of policy implementation. The study revealed the complex situation whereby welfare workers helping immigrants to obtain services express uncertainty whether they are really helping, or potentially harming, their clients under the public charge ruling.…”
Section: Overview Of Immigration Policiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Policies about immigration and access to welfare systems for immigrants are constantly evolving, leading to confusion and inconsistent implementation. Lanfranconi et al (2020) examined the inclusionary and exclusionary mechanisms that are imposed through regimes, practices, and discourses at multiple levels of policy implementation. The study revealed the complex situation whereby welfare workers helping immigrants to obtain services express uncertainty whether they are really helping, or potentially harming, their clients under the public charge ruling.…”
Section: Overview Of Immigration Policiesmentioning
confidence: 99%
“…A common attitude among immigrants and their children is wanting to conform to the U.S. norms of work ethic and self-sufficiency. Recent immigrants, especially first-generation immigrants, display self-motivation to find a job as quickly as possible and comply with interventions (Lanfranconi et al, 2020). Involvement with the welfare system could be construed as a weakness and a source of shame, so immigrants might work very hard to succeed, gain pride, support other families back home relying on their aid, and avoid unpleasant encounters with welfare agencies.…”
Section: Protective Factors and Strengths Associated With Immigrants ...mentioning
confidence: 99%
See 1 more Smart Citation
“…This study uses data that were collected as a part of a broader mixed-methods study on "Social Equity Within California's WTW Pro-gram" (see Chang et al, 2020;Lanfranconi & Basaran, forthcoming;Lanfranconi et al, 2020aLanfranconi et al, , 2020b. The study adopts a qualitative comparative case study design by juxtaposing two "most different" cases (Flyvbjerg, 2006).…”
Section: Case Studymentioning
confidence: 99%